The blind colt - Rounds, Glen, 1906-2002 (New York : Holiday House, 2021)
Relates the adventures of a blind colt as he roams with a band of mustangs and is eventually adopted and trained as a saddle horse by ten-year-old Whitey.
Keywords: Horses -- Juvenile fiction; Horses -- Fiction; Animals with disabilities -- Fiction; West (U.S.) -- Fiction; Animal fiction